Fock space localisation in the disordered transverse-field Ising Model - Creed, I (2023)
In recent years, there has been considerable interest both theoretically and experimentally in the field of many-body localisation (MBL). This thesis considers aspects of many-body localisation in Fock-space for the one-dimensional disordered transverse-field Ising model, focusing on the behaviour in the ergodic and the MBL phases.